O apoio psicopedagógico ao paciente em tratamento prolongado: uma investigação sobre o processo de aprendizagem no Hospital de Clínicas da Universidade Federal de Uberlândia - Ferreira, Pérsia Karine Rodrigues Kabata (2011)
The main purpose of the present study was to investigate the role of Psychopedagogical support in hospital environment for the recovery, the development and the learning process of patients in situation of prolonged treatment. More specifically, the study aimed at finding out whether it was possible, through Psychopedagogical assistance, to favor the development of patients‟ learning process, as well as their recovery and reintegration processes. Taking into account the main concerns that led to the research problem, a case study was carried out in the Hospital de Clínicas de Uberlândia Universidade Federal de Uberlândia (HCU-UFU). In order to allow a better understanding of the whole process, a description of the study and a general overview of the history of what is called hospital classes , a new modality of educational assistance which is being offered in that context, is presented. Those hospital classes represent the beginning and the first step towards the educational actions which are being carried out in the context of the HCU-UFU. Therefore, a detailed description about them is necessary for a better understanding of the constitution of the Psychopedagogical assistance in that context. Based on the theoretical background used for the research, we sought to better understand the possibilities, as well as the limits and the challenges, of this new field of work for the psycho-pedagogues. Results, in a general sense, revealed that the subjects who took part in the research showed some progress, in terms of their learning process. According to the study, patients with chronic renal failure, in the hemodialysis unit, in general, are not incapable of learning, and if, on the one hand, the treatment they are going through may render difficulties, on the other hand it does not prevent or impede the development of patients‟ natural curiosity and disposition to learn. On the contrary, it may even benefit the mediation which the psychopedagogue provides in the dynamics of treatment as well as in the patient‟s life outside the hospital. It was possible to provide the patients with the opportunity to construct knowledge and to optimize their learning processes concerning reading and writing skills, together with the involvement of cognitive and affective aspects, such as the exchange of information about their feelings and perceptions of the hospital and the routine of their treatment. The insertion of Psychopedagogical assistance in the hospital is not a linear process. The tendency among people to think of the hospital as place exclusively devoted to providing treatment for patients‟ diseases is still very strong, and patients are identified primarily by their pathology and their condition. A holistic look at the hospitalized patient is still an achievement to be conquered.